Polydeoxyribonucleotide, an Adenosine-A2A Receptor Agonist, Preserves Blood Testis Barrier from Cadmium-Induced Injury - Squadrito, Francesco; Micali, Antonio; Rinaldi, Mariagrazia; Irrera, Natasha; Marini, Herbert; Puzzolo, Domenico; Pisani, Antonina; Lorenzini, Cesare; Valenti, Andrea; Laurà, Rosaria; Germanà, Antonino; Bitto, Alessandra; et al. (Frontiers in Pharmacology, 2017)
Cadmium (Cd) impairs blood-testis barrier (BTB). Polydeoxyribonucleotide (PDRN), an adenosine A2A agonist, has positive effects on male reproductive system. We investigated the effects of PDRN on the morphological and functional changes induced by Cd in mice testes. Adult Swiss mice were divided into four groups: controls administered with 0.9% NaCl (1 ml/kg, i.p., daily) or with PDRN (8 mg/kg, i.p. daily), animals challenged with Cd chloride (CdCl2) (2 mg/kg i.p, daily) and animals challenged with CdCl2 (2 mg/kg i.p., daily) and treated with PDRN (8 mg/kg i.p., daily). Experiments lasted 14 days. Testes were processed for biochemical, structural and ultrastructural evaluation and hormones were assayed in serum. CdCl2 increased pERK 1/2 expression and Follicle Stimulating Hormone (FSH) and Luteinizing Hormone (LH) levels; it decreased testosterone (TE) and inhibin-B levels and induced structural damages in extratubular compartment and in seminiferous epithelium, with ultrastructural features of BTB disruption. Many TUNEL-positive germ cells were present. CdCl2 increased tubular TGF-β3 immunoreactivity and reduced claudin-11, occludin and N-cadherin immunoreactivity. PDRN administration reduced pERK 1/2 expression, FSH and LH levels; it increased TE and inhibin-B levels, ameliorated germinal epithelium changes and protected BTB ultrastructure. Few TUNEL-positive germ cells were present and the extratubular compartment was preserved. Furthermore, PDRN decreased TGF-β3 immunoreactivity and enhanced claudin-11, occludin and N-cadherin immunoreactivity. We demonstrate a protective effect of PDRN on Cd-induced damages of BTB and suggest that PDRN may play an important role against Cd, particularly against its harmful effects on gametogenesis.